MANAGEMENT OF APRICOT SHOT HOLE DISEASE (Wilsonomyces carpophilus) USING TRUNK INJECTION DELIVERY SYSTEM - Azhar Hussain; Sartaj Ali; Muhammad Muhammad; Wasim Akram; Aq; ee; Abbas (Journal of Animal and Plant Sciences, 2025)
Shot-hole disease (SHD) is a widely spread and devastating disease of apricots that leads to severe yield loss and poor quality of fruit. However, limited research has been conducted on SHD management using trunk injection delivery systems in Gilgit-Baltistan, Pakistan. In this study, the efficacy of individual (Bordeaux mixture (BM), Capparis spinosa (CP), Mentha piperita (MP), Artemisia vulgaris; (AV) and in combination (BM + MP, BM + CP, BM + AV) of BM and plant extracts treatments were evaluated against SHD. The experiment was conducted in the apricot orchards during 2022-23 as a complete randomized block design under factorial arrangement. The analysis of variance showed significant (P ≤ 0.5) variation in SHD incidence among the treatments. Among individual treatments, BM was the most effective against SHD with 27.4% incidence, followed by AV (39.8%), whereas CP and MP were moderately efficacious (means: 43.03% and 43.14%, respectively). The control treatment showed extremely high disease occurrence (73.77%). Moreover, the highest effectiveness was found in the combination treatments. BM + MP reduced the disease incidence rate to 29.67%, followed by BM + CP (47.32%), which provided a more stable form of disease suppression. Hence, BM alone and in combination with plant extracts effectively reduce SHD. These results highlight the potential of plant-based trunk injection treatments for SHD management, with BM + MP offering the most effective control.
Keywords: Apricot; Bordeaux mixture; cultivars; plant protective material; shot hole disease; trunk injection